The Value of Diagnostic Laparoscopy in Gastroenterology (Due to 3000 cases) - Atilla ÖKTEN; Süleyman YALÇIN; Güngör BOZTAŞ; Oktay YEĞİNSÜ; Sadakat ÖZDİL; Zeynel MUNGAN; Yılmaz ÇAKALOĞLU; Sebahattin KAYMAKOĞLU; İlhan ULAGAY (Turkish Journal of Gastroenterology, 2020)
-